Hegemonic currencies during the crisis: The dollar versus the euro in a cartalist perspective - David Fields; Matías Vernengo (Levy Economics Institute of Bard College, 2011)
This paper suggests that the dollar is not threatened as the hegemonic international currency, and that most analysts are incapable of understanding the resilience of the dollar, not only because they ignore the theories of monetary hegemonic stability or what, more recently, has been termed the geography of money; but also as a result of an incomplete understanding of what a monetary hegemon does. The hegemon is not required to maintain credible macroeconomic policies (i.e., fiscally contractionary policies to maintain the value of the currency), but rather to provide an asset free of the risk of default. It is argued that the current crisis in Europe illustrates why the euro is not a real contender for hegemony in the near future.
Keywords: F31; F33; F55; 330; Dollar; Euro; international currency; Reservewährung; Internationales Währungssystem; Währungswettbewerb; Finanzmarktkrise; US-Dollar; Euro